209k views
4 votes
Hi. I need help with these questions.
See image for question.

Hi. I need help with these questions. See image for question.-example-1
User Rob Paller
by
5.1k points

1 Answer

0 votes

Answer:

Explanation:

Plug in the stated values for x

(a) 2(1)^4 + 3(1)^3 - (1)^3 + 2(1) - 3

2 + 3 - 1 + 2 - 3 = 1 + 2 = 3

f(1) = 3

(b) 2(-1)^4 + 3(-1)^3 - (-1)^2 + 2(-1) - 3

2 * 1 + 3(-1) - 1 + 2(-1) - 3

2 + -3 -1 -2 - 3 = 2 - 9 = -7

f(-1) = -7

(c) 2(0) + 3(0) - 0 + 0 - 3

0 - 3 = -3

f(0) = -3

d) 2(-1/2)^4 + 3(-1/2)^3 - 2(-1/2) - 3

1/8 - 3/8 - (-1/2)^2 - 2 * 1/2 - 3

16/4 - 1/4 - 1/4 = -16-1-1/4 = -18/4

f(-1/2) = -9/2

User Giorgos Manoltzas
by
5.7k points